A new species of the genus Tuberfemurus (Orthoptera: Tetrigoidea: Cladonotinae) with comments on the characters of mitochondrial genome - Wang, Meng-Qi; Deng, Yao; Guan, De-Long; Mao, Ben-Yong; Li, Miao (Zootaxa, 2021)
A new species, Tuberfemurus viridulus sp. nov. is described and illustrated with photographs. The new species is similar to T. torulisinotus Deng, 2019, but differs from the latter by broader vertex, invisible frontal costa in profile, distinctly truncate apex of hind pronotal process, and two large triangular projections on lower outer carinae of hind femur. An updated key to species of Tuberfemurus is provided. Simultaneously, the complete mitochondrial genome of Tuberfemurus viridulus sp. nov. is sequenced and analyzed. The total length of the assembled mitogenome is 15,060 bp with 37 typical mitochondrial genes and a non-coding region (A + T-rich region). The order and orientation of the gene arrangement pattern are identical to that of most Tetrigoidea species. All PCGs initiate with the standard start codon of ATN, except ATP6 with GAC and ND1 with TTG; and terminate with the complete stop codon (TAA/TAG) or with an incomplete T- codon. This data could provide the genome information available for Tetrigoidea and facilitate phylogenetic studies of related insects.